An maith leat an Ghaeilge? An analysis of variation in primary pupil attitudes to Irish in the Growing Up in Ireland study - Devitt, Ann; Condon, Joe; Dalton, Gene; O'Connell, Jane; Ní Dhuinn, Melanie (My University, 2018)
This paper presents an analysis of primary schoolchildren's attitudes to the Irish language, Gaeilge, in the context of national policy in the Republic of Ireland. In particular, the study examines the factors (social, cultural, cognitive and organisational) that may be related to a pronounced excess in disengagement with Irish over and above general engagement with schooling. The data derives from the nine-year-old child cohort of the national longitudinal study of children, the Growing Up in Ireland (GUI) survey. Unlike previous findings in relation to general engagement with school, excess disengagement with Irish is not found to be related to socio-economic or ethnic factors, factors related to teacher profile, training, self-efficacy or style or school ethos. As expected, children with less exposure to spoken Irish in school or at home are more likely to show excess disengagement with the language. Literacy activity, special education needs and school patronage are also found to be related to excess disengagement. Significant random effects indicate the importance of the individual teacher and school in the development of pupil engagement with Irish. The current study presents a timely perspective on attitudes to Irish among the younger population and possible implications for policy.
PUBLISHED
Keywords: Irish language; Gaeilge; Motivation; Minority languages; Bilingualism; Biliteracy; Irish Language; Minority language education and maintenance; attidude & motivational studies of second-language learners; language attitudes